Women, gender, and radical religion in early modern Europe - Brown, Sylvia Monica, 1966- (Brill, 2007)
This collection of essays explores the role of women and gender in a broad range of 'radical' religious movements of the post-Reformation.
Keywords: Börngen, ...; Europa; Women in Christianity -- Europe -- History.; Christian women -- Religious life -- Europe.; Women -- Religious life -- Europe.; Sex role -- Religious aspects -- Christianity -- History.; Femmes dans le christianisme -- Europe -- Histoire.; Femmes -- Vie religieuse -- Europe.; Rôle selon le sexe -- Aspect religieux -- Christianisme -- Histoire.; RELIGION -- Religious Intolerance, Persecution & Conflict.; RELIGION -- Christianity -- History.; Women and religion -- Europe -- History.; Radicalism -- Religious aspects.; Radicalism -- Europe.; Christian women -- Religious life; Sex role -- Religious aspects -- Christianity; Women in Christianity; Women -- Religious life; Europe; Radikalismus; Religion; Frau; Vrouwen.; Christendom.; Radicale bewegingen.; Europa (geografie); History